The Effectiveness of Postpartum Structured Counseling on Self-Warning Knowledge of Postpartum Mothers at the Ome Inpatient Health Center - Eka Aida Fitri Boyke; Rosyidah Alfitri (Jurnal Siti Rufaidah, 2025)
Background: The postpartum period is a critical phase for maternal health, as mothers are vulnerable to various complications that may lead to serious morbidity or mortality if not detected early. Self-warning knowledge regarding danger signs during the postpartum period plays an essential role in enabling mothers to recognize abnormal conditions and seek timely health care. However, limited knowledge and inadequate counseling remain common challenges in postpartum services. Structured postpartum counseling is expected to improve mothers’ understanding of self-warning signs and enhance early detection of complications. Objective: This study aimed to determine the effectiveness of structured postpartum counseling on self-warning knowledge among postpartum mothers at the Ome Inpatient Health Center. Methods: This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 16 postpartum mothers selected using a total sampling technique. Data were collected using structured questionnaires to assess mothers’ knowledge of postpartum self-warning signs before and after receiving structured counseling. The counseling intervention was delivered using standardized educational materials. Data were analyzed using the Chi-square test to determine the effectiveness of structured postpartum counseling on self-warning knowledge. Results: The results showed an increase in self-warning knowledge among postpartum mothers after receiving structured counseling. Statistical analysis using the Chi-square test indicated a p-value of 0.000 (p < 0.05), demonstrating a statistically significant effect of structured postpartum counseling on improving postpartum mothers’ self-warning knowledge. Conclusion: Structured postpartum counseling is effective in enhancing self-warning knowledge among postpartum mothers. The implementation of structured and continuous counseling during the postpartum period is recommended to support early detection of complications and improve maternal health outcomes.